The Relationship Between Katseye Celebrity Endorsers and Brand Image Gap Among Generation Z in Indonesia - Putri, Jihan Tertia Nugraha; Dida, Susanne; Sjoraida, Diah Fatma (Multi Discere Journal, 2026)
The use of celebrity endorsers as a marketing strategy is aimed at representing values that are relevant to the audience, especially Generation Z, who have high preference for diversity and inclusivity. Mismatches between endorser values and audiences preferences can impact brand image. Furthermore, comparisons show that GAP still faces challenges in brand loyalty related to brand image. In this context, GAP chose Katseye with its multicultural and inclusive background, but the effectiveness of this strategy not been empirically proven. This study aims to determine the relationshop between the credibility of celebrity endorser Katseye and GAP’s brand image among Generation Z in Indonesia, measured by the dimensions of expertise, trustworthiness and attractiveness. The use of celebrity endorsers as a marketing strategy is aimed at representing values ​​relevant to the audience, especially Generation Z, who have a high preference for diversity and inclusivity. Mismatches between endorser values ​​and audience preferences can impact brand image. Furthermore, comparisons show that GAP still faces challenges in brand loyalty related to brand image. In this context, GAP chose Katseye with its multicultural and inclusive background, but the effectiveness of this strategy in shaping brand image among Generation Z has not been empirically proven. This study aims to determine the relationship between the credibility of celebrity endorser Katseye and GAP's brand image among Generation Z in Indonesia, measured by the dimensions of expertise, trustworthiness, and attractiveness. This study uses a quantitative approach with a correlational method. The sample of this study was 140 Generation Z respondents in Indonesia who had been exposed to GAP's advertisement with Katseye on TikTok. Data were collected using a questionnaire with a Likert scale and analyzed using Spearman's correlation test using SPSS software. The results show a significant relationship between the credibility of celebrity endorser Katseye and GAP's brand image (0.696). More specifically, expertise shows a moderately relationship (0.617), trustworthiness shows a moderately relationship (0.669), and attractiveness shows a moderately relationship (0.501) with brand image. The conclusion of this study shows that celebrity endorser credibility plays a role in forming brand image, although the contribution of each dimension is different.